Comparative study of spherical dimple and bump effects on the tribological performances of journal bearing. (January 2019) - Gui, Chao; Meng, Fanming
In the present study, tribological performances of journal bearings with the representative spherical dimples and bumps are compared numerically. In doing so, the hydrodynamic pressure of the lubricant is solved by the Reynolds equation considering the lubricant cavitation effect. Meanwhile, the elastic deformation is calculated by the continuous convolution fast Fourier transform method. The enhanced load-carrying capacity and the reduced friction force occur only when the dimples are located at pressure rising part of the bearing. The bumps located at the pressure falling part can enhance the load-carrying capacity but increase the friction force. The above dimple and bump effects change at the varied feature sizes and intervals.